2005
DOI: 10.1029/2004jb003085
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the magnetization low of the Lucky Strike hydrothermal vent using surface magnetic data

Abstract: Two surface magnetic surveys, covering the Lucky Strike hydrothermal area, are merged into a single magnetic anomaly description, which, when inverted in the presence of topography, shows a magnetization low at the segment center, close to the central volcano, in the middle of which is located the hydrothermal vent. To test if this magnetization is in any way connected with the hydrothermal vent field, we devised a method to distinguish a “regional” field that can be attributed to the “normal” spreading geomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…The vents provide a significant contribution to the near‐axis heat flux [ Jean‐Baptiste et al , 1998], and the observed heat flow measurements are consistent with fluid flow from the ridge flank toward the ridge axis [ Lucazeau et al , 2006]. The magnetic anomaly observed at the Lucky Strike segment is axis parallel, and a low magnetization anomaly underneath the Lucky Strike hydrothermal field can be interpreted as demagnetization of the rocks by focalized hydrothermal flow [ Miranda et al , 2005].…”
Section: Lucky Strike Segmentmentioning
confidence: 86%
“…The vents provide a significant contribution to the near‐axis heat flux [ Jean‐Baptiste et al , 1998], and the observed heat flow measurements are consistent with fluid flow from the ridge flank toward the ridge axis [ Lucazeau et al , 2006]. The magnetic anomaly observed at the Lucky Strike segment is axis parallel, and a low magnetization anomaly underneath the Lucky Strike hydrothermal field can be interpreted as demagnetization of the rocks by focalized hydrothermal flow [ Miranda et al , 2005].…”
Section: Lucky Strike Segmentmentioning
confidence: 86%
“…It is underlain by an axial magma chamber 3.4 km below the seafloor (Singh et al, 2006) and hosts an active hydrothermal field at its summit (Langmuir et al, 1997). Several volcanic ridges spread north and south from this central volcano suggesting along axis diking, while magnetic data suggest that magmatic accretion in the center of the Lucky Strike segment is Andres et al (2004), Blichert-Toft et al (2005), Castillo and Batiza (1989), Chauvel and BlichertToft (2001), Debaille et al (2006), Dosso et al (1991), Dosso et al (1993), Dosso et al (1999), Douglass et al (1999), Frey et al (1993), Fontignie and Schilling (1996) presently focused in a narrow graben at the top of the central volcano (Miranda et al, 2005). This area has been well studied since the hydrothermal field discovery in 1992 (Langmuir et al, 1997), with a uniquely dense sampling among slow-spreading segments; more than 200 basaltic samples have been collected with dredges, wax cores, submersibles, and other deep-sea vehicles.…”
Section: Geological Setting and Small Scale Samplingmentioning
confidence: 96%
“…Scheirer et al [2000] have described the three summit cones as made of series of subparallel, N10-N30 trending ridges and troughs, with a relief of 10 to 20 m. These authors show a neo-volcanic zone that is 1 km wide and extends to the NNE and SSW from the area of the lava lake. This definition of the neovolcanic axis appears to fit with magnetic anomalies modeled from shipboard surveys [Miranda et al, 2005].…”
Section: Lucky Strike Hydrothermal Fieldmentioning
confidence: 99%